Identifying tumor antigens and immune subtypes of renal cell carcinoma for immunotherapy development - Chen, Xinglin; Zhang, Tongtong; Zhai, Xinyu; Wan, Zhong; Ge, Minyao; Liu, Chengzong; Tan, Mingyue; Xu, Dongliang (Frontiers in Immunology, 2022)
Abstract Renal cell cancer (RCC) is one of males' leading causes of death. Messenger ribonucleic acid (mRNA) vaccines may be an attractive means to achieve satisfactory results. Cancer immunotherapy is a promising cancer treatment strategy. However, immunotherapy is not widely used in renal cell carcinoma, as only a few patients show a positive response. The present study aimed to identify potential antigens associated with renal cell carcinoma to develop an anti-renal cell carcinoma mRNA vaccine. Moreover, the immune subtypes of renal cell carcinoma cells were determined. The Cancer Genome Atlas (TCGA) analysis revealed gene expression profiles and clinical information. Antigen-presenting cells infiltrated the immune system using TIMER tool (http://timer.cistrome.org/). GDSC (Genomics of Drug Sensitivity in Cancer) data were used to estimate drug sensitivity. The 13 immune-related genes discovery could be a target for immunotherapy in renal cell carcinoma patients, as they were associated with a better prognosis and a higher level of antigen-presenting cells. These immune subtypes have significant relationships with immunological checkpoints, immunogenic cell death regulators, and RCC prognostic variables. Furthermore, DBH-AS1 was identified as potential antigens for developing an mRNA vaccine. The CCK8 assay demonstrated that the proliferative capacity of 786-O and Caki-1 cells overexpressing DBH-AS1 was higher than control group. In addition, transwell assay revealed that 786-O and Caki-1 cells overexpressing DBH-AS1 showed higher invasion capacity compared with empty vector. This study provides a theoretical basis for the development of mRNA vaccines. Our findings suggest that DBH-AS1 could be potential antigens for developing RCC mRNA vaccines. Keywords: DBH-AS1; immunotherapy; mRNA vaccine; renal cell carcinoma; immune subtypes